A study on job satisfaction of MISC agencies towards their job / Siti Munirah Mohd Hamyah - Mohd Hamyah, Siti Munirah (2009)
Job satisfaction has been defined as a pleasurable emotional state resulting from the appraisal of one’s job, an affective reaction to one’s job and an attitude towards one’s job. Weiss (2002) has argued that job satisfaction is an attitude but points out that researchers should clearly distinguish the objects of cognitive evaluation which are affect (emotion), beliefs and behaviors.http://en.wikipedia.org/wiki/Job_satisfaction ‐ cite_note‐3 This definition suggests that we form attitudes towards our jobs by taking into account our feelings, our beliefs, and our behaviors. Investigated by several disciplines such as psychology, sociology, economics and management sciences, job satisfaction is a frequently studied subject in work and organizational literature. This research was conducted for the purposed of job satisfaction at MISC Agencies Sdn Bhd (MISA). The main objective of this research was identify the factors that influence job satisfaction level among employee in MISA. The respondent of this study was employee of MISA. 89 questionnaire had been distributed to the employee of MISA. In this study, we used survey and observation, questionnaire techniques and others secondary data such as reports, database and so on for data collection. Based on reliability test, respondent profile, frequency, correlations, cross tab tabulation and Chi-squared test, a clear findings and result is observed. The findings showed that most of the staffs have moderate of satisfaction with the payments, rewards, working condition and working itself. The researcher is also able to give some recommendations and suggestion on how to improve and increase job satisfaction of the staffs after analysis, findings and interpretation. The conclusion of this study was the outcome from the survey analysis and findings. Through the research, it shows that majority of the employee who work in MISA achieve moderate job satisfaction level.